ANALISIS PERAN GURU PENGGERAK DALAM MENERAPKAN PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - Agustin, Taski Adelia; A. Syachruroji; Pribadi, Reksa Adya (Jurnal Pendidikan Dasar, 2025)
Education aims to shape a whole person, differentiated learning is one approach that accommodates various learning needs such as readiness, interests and profiles. Differentiated learning in its application is not easy, this is where the important role of the driving teacher is, because the driving teacher has received special training that equips teachers with both knowledge and skills to accommodate the diverse learning needs of students. This study aims to describe: 1) The profile of the driving teacher. 2) The role of the driving teacher in planning and implementing differentiated learning. 3) Implications of the role of the driving teacher in implementing differentiated learning. This study uses a descriptive qualitative method, with data collection techniques in the form of interviews, observations and documentation. The informants in this study were the driving teacher and students in grades III, V and VI. The results of the study show that: 1) The profile of the driving teacher at SDN Cilegon II shows that teachers have diverse educational backgrounds, teachers are actively involved in professional development activities and make a real contribution to creating positive changes in schools. 2) In planning, teachers play a role in identifying learning needs and designing teaching modules with a differentiated approach, and in implementation, teachers act as guides, directors, facilitators, innovators, and motivators. 3) The implications of the role of the driving teacher have a positive impact on increasing self-esteem, motivation and interest in learning, as well as social and collaborative skills of students.